North Kalimantan Economic Policies Analysis Using Multicollinearity Test Among Government Economy Indicators and Performances - Rafiqoh, Rafiqoh; Viddy, Arkas; Karunia, Erick (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The purpose of this study is to investigate the inter correlate between economy indicators and performance in North Kalimantan Indonesia. This research is in North Kalimantan Indonesia whereas it is consisting of 4 regencies such as Nunukan, Bulungan, Malinau and Tana Tidung, and 1 district namely Tarakan. This study is quantitative research using Multycolinier test using Pearson Correlation or one of classic assumption test. There several economy indicators and performance will be examined such as economic growth, inflation, poverty rate, unemployment and human development index. This study found that there are two variables have multycolinier namely between unemployment and human development index with -0.873. It can be concluded that unemployment is already represents by human development index or government policies can focused on increasing human development index and it will decrease the unemployment rate itself.